HIT maintains performance during the transition period and improves next season performance in well-trained cyclists - Ronnestad, B. R.; Askestad, A.; Hansen, J. (European Journal of Applied Physiology, 2014)
Purpose To investigate the effects of combining low-intensity endurance training (LIT) with one high-intensity endurance training (HIT) session every 7-10 days (EXP, n = 7) vs. traditional approach focusing on LIT (TRAD, n = 6) during the transition period. The effects of different training strategies during the transition period were investigated after the transition period and at the beginning of the subsequent competition season.Methods Well-trained cyclists were tested after the competition season, after an 8-week transition period, and after a 16-week preparatory period, before the subsequent competition season. The only difference between groups was a larger time with HIT during the transition phase in EXP.Results It was very likely that EXP had a larger impact on power output at 4 mmol L-1 [la-] after both the transition period and after the preparatory period than TRAD [between-group change (90 % CI): 10.6 % (8.2 %) and 12.9 % (11.9 %), respectively]. It was very likely that EXP had a larger impact on mean power output in the 40-min all-out trial after the transition period than TRAD [between-group change 12.4 % (7.6 %)]. EXP was also likely to have a larger improvement in the 40-min trial performance from pre-test to after the preparatory period than TRAD [between-group change 6.0 % (6.6 %)]. Conclusion The present findings suggest that HIT sessions should be incorporated during the transition phase to avoid reduction in fitness and performance level and thereby increase the likelihood of improved performance from the end of one season to the beginning of the subsequent season.